Profile Analysis of Heart Rate Recovery after Maximum Exercise in Student Athletes in Dynamic Sports - DR. Oce Wiriawan S.Pd (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Destination: The main objective of this study was to determine the Heart Rate Recovery (HRR) profile after performing Maximal Exercise (EM). Method: 86 student athletes (age: 18.6 ± 2.69 years) who came from dynamic sports, running and jumping athletics (n = 9), from basketball (n = 5), from volleyball (n = 17), from hockey (n = 22), from roller skating (n = 15), from beach volleyball (n = 15), and from tennis (n = 3). Performs a 30m sprint speed test. Furthermore, HRR is measured using the Polar type H10 tool using the Polar Team monitor system. Furthermore, HRR was recorded at 1, 2, 3, 4, and 5 minutes just after doing maximal exercise. Furthermore, using the paired t-test and Friedman's test to see the significance of the difference in value every minute. Furthermore, to obtain a sticky heart rate recovery profile, the HRR is calculated with the maximum heart rate (HR). Result: It was found that the results were significant differences in the HRR values 1, 2, and 3 χ2F (2) = 170.02, p <0.001 using the Friedman's test. Significant differences were also found in the HRR values of 4 and 5 using the paired sample t-test HRR 4 (Mean = 104.07, SD = 8.838) and HRR 5 (Mean = 95.35, SD = 7.232) under conditions; t (85) = 15,618, p = 0.000. Furthermore, so that the difference in HRR is significant, a further test is carried out by looking for Δ HRR1,2,3,4, and 5 with HRmaximal and the value of nilaiHRR 1 is 19.18 ± 6.6, then sequentially Δ HRR 2:29.45 ± 7.10,Δ HRR 3: 38.06 ± 6.88, Δ HRR 4:43.72 ± 5.54, andΔ HRR 5:48.44 ± 4.67. Conclusion: In this study it can be proven that the HRR profile of student athletes can be used as an indicator of athletes' readiness to accept and participate in training programs..